Tissue-specific laser surgery: Hard tissue differentiation by diffuse reflectance spectroscopy ex vivo - Zam, Azhar; Stelzle, Florian; Nkenke, Emeka; Tangermann-Gerk, Katja; Schmidt, Michael; Adler, Werner; Douplik, Alexandre (Optics InfoBase Conference Papers, 2009)
Diffuse reflectance spectroscopy provides a straightforward and simple approach for optical tissue differentiation. The results obtained show a potential for differentiating hard tissues as guidance for tissuespecific laser surgery. © 2009 Optical Society of America.
Created from Fastlane, Scopus look-up